Kamerschatten : tentoonstelling in elf woonhuizen van 's-Hertogenbosch met als thema Het interieur. - Ter Borg, Lucette; Doorman, Maarten; Faber, Nathalie; Gevers, Ine; Keijer, Kees; Kemper, Margriet; Smallenburg, Sandra; Teeuwen, Marjan; Wagemans, Fred; van Driel, Anne; van Mechelen, Brigitte ('s-Hertogenbosch : Stichting KW14, 1999)
Pfannenmüller, Urs ; Clevis, Krien ; Martens, Ton ; Teeuwen, Marjan ; Gartz, Wineke ; Mattijssen, Erik ; van Tellingen, Maurice ; van Gils, John ; van den Assem, Marjolijn ; van Osch, Paul ; Atelier van Lieshout ; Reijers, Zeger ; Berghs, Antoine ; Adriaans, Léon ; Robbé, Lon ; Rouppe van der Voort, Alexandra ; Killaars, Fransje ; Mandersloot, Frank ; van Schaijk, Mieke ; Tummers, Arno ; Seegers, Ellen ; Brand, Eelco ; Sissingh, Bert ; Doorenweerd, Jeroen ; Walvoort, Anneke ; Verwaaijen, Cécile ; Egberts, Otto ; Mik, Aernout
biog. per kunstenaar 1 p.
Nederlands
Kamerschatten, Stichting KW14, 's-Hertogenbosch, 12 - 28 november 1999
boek